Preparation Of Activated Carbon From Rice Husk By Microwave Irradiation For Adsorption Of Methylene Blue Dye - Ishak, Siti Khairunnisa (Universiti Sains Malaysia, 2017)
In this study, rice husk based activated carbon (RHAC) was prepared for the removal of methylene blue (MB) dye. Rice husk was used to prepare RHAC through physical activation process which involved microwave irradiation and carbon dioxide (CO2) gasification. The effect of initial dye concentration (25-500 mg/L), contact time (1-24 h) and solution temperature (30-60°C) were evaluated. The optimum preparation conditions were obtained from response surface methodology (RSM) at radiation power of 440 W and activation time of 4.28 minutes which have resulted in 83.93% MB removal and 32.55% RHAC yield. Optimized RHAC sample has surface area of 668.30 m2/g, pore volume of 0.348 cm3/g and fixed carbon content of 70.34. The pore of RHAC was mesoporous type with average pore diameter of 4.42 nm. The adsorption equilibrium data is to be fitted into three isotherm models which are Langmuir, Freundlich and Temkin. Adsorption equilibrium and kinetic of MB on RHAC were best fitted by Freundlich isotherm and pseudo-second order kinetic models. From thermodynamic study, the adsorption process of MB onto RHAC was endothermic in nature and spontaneous process.